PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP STRES KERJA PADA KARYAWAN PUSKESMAS KEDIRI LOMBOK BARAT NTB - ROSYIA WARDANI (Akuntansi research UGR, 2020)
The purpose of this study is (1) To find out the significant effect of workload on work stress on employees of the Kediri Community Health Center. (2) To find out the significant influence of work environment on work stress on the employees of Kediri Health Center. This type of research used in this research is associative research. Data collection techniques used in this study were questionnaires. In this study the determination of the sample was carried out using the probability sampling method with a stratified random sampling procedure, which means taking a sample with regard to strata or levels in the population of Kediri Community Health Center employees as many as 46 people. Data analysis technique that will be used in this research is Multiple Linear Regression Analysis. Based on the analysis that has been done, it can be concluded that (1) Workload has a significant effect on Job Stress. (2) The Work Environment has a significant effect on the Work Stress of Kediri Community Health Center employees. Based on the results of research that has been done, the authors provide a suggestion that real continuous efforts are needed to reduce stress levels of employees in the workplace for example by providing adequate work infrastructure, ensuring sufficient numbers of employees to handle various jobs.